0276 Does Losing Sleep Unleash Anger?. (27th May 2020) - Krizan, Z; Miller, A; Hisler, G
Abstract: Introduction: Sleeping is understood as essential to affective function, yet little is known about how sleep shapes more specific and contextualized emotional responses besides anxiety and depression, such as anger. Anger itself involves arousal and can disrupt sleep. To examine the causal role of sleep in anger, a daily-diary study and an experimental study tested whether shortened sleep amplifies angry feelings, while exploring mediating mechanisms of this influence. Methods: The daily-diary study (N = 202) collected daily reports of last-night's sleep, daily stressors, and state anger across one month from college students, examining sleep and anger within everyday life. The experimental laboratory study (N = 147 community residents) examined changes in anger experienced during aversive noise following random assignment to either at-home sleep restriction (by about 5 hours across 2 nights), or to individuals' regular schedule. Results: In the daily-diary study, individuals experienced more anger on days following less sleep than their usual, with half of this effect attributed to the increased frequency of stressors experienced on such days, and somewhat independently from the effect of sleep duration on negative affect more generally. In the experimental study, well-slept individuals adapted to noise and reported less anger and negative affect after 2 days. In contrast, sleep-restricted individuals exhibited higher and increased anger responses. The impact of sleep restriction on anger held even after accounting for negative emotions more generally. Subjective sleepiness accounted for most of the experimental effect of sleep loss on anger. Conclusion: Together, these results provide compelling evidence that lost sleep amplifies anger in both the laboratory and everyday life, while also pointing to short-term (subjective sleepiness) and mid-term (stress) mediators of these influences. The findings also point to the value of examining specific emotional reactions (and their regulation) in the context of sleep disruption, alongside affect more broadly. Support: N/A